THE ORGANIC CONNECTION BETWEEN MODERN PSYCHOLOGY AND PEDAGOGY (American Journal of Interdisciplinary Research and Development, 2024)
This article explores the deep and complex relationship between modern psychology and pedagogy, shedding light on how advances in psychological research have influenced educational practice. The integration of psychological principles into pedagogy has revolutionized teaching methods, curriculum development, and student learning outcomes. By examining key theories and empirical evidence, this article illuminates the symbiotic nature of psychology and pedagogy, emphasizing the importance of understanding psychological processes in optimizing the educational experience for students.